Comparison of extractive distillation flowsheets for methanol–tetrahydrofuran–water mixtures - V. M. Raeva; A. M. Dubrovsky (Тонкие химические технологии, 2020)
Objectives. Synthesis and comparative analysis of the extractive distillation flowsheets for aqueous mixtures of solvents utilized in pharmaceutical industries using the example of a methanol−tetrahydrofuran−water system with various compositions. The ternary system contains two minimally boiling azeotropes that exist in a vapor–liquid phase equilibrium. To evaluate the selective effect of glycerol, the phase equilibria of the methanol–tetrahydrofuran–water and methanol–tetrahydrofuran–water–glycerol systems at 101.32 kPa were studied.Methods. The calculations were carried out in the Aspen Plus V.9.0 software package. The vapor–liquid equilibria were simulated using the non-random two-liquid (NRTL) equation with the binary interaction parameters of the software package database. To account for the non-ideal behavior of the vapor phase, the Redlich–Kwong equation of state was used. The calculations of the extractive distillation schemes were carried out at 101.32 kPa.Results. The conceptual flowsheets of extractive distillation are proposed. The flowsheets consist of three (schemes I–III) or four (scheme IV) distillation columns operating at atmospheric pressure. In schemes I and II, the extractive distillation of the mixtures is carried out with tetrahydrofuran isolation occurring in the distillate stream. Further separation in the schemes differs in the order of glycerol isolation: in the third column for scheme I (traditional extractive distillation complex) or in the second column for scheme II (two-column extractive distillation complex + methanol/water separation column). Sсheme III caters to the complete dehydration of the basic ternary mixtures, followed by the extractive distillation of the azeotropic methanol–tetrahydrofuran system, also with glycerol. Sсheme IV includes a preconcentration column (for the partial removal of water) and a traditional extractive distillation complex.Conclusions. According to the criterion of least energy consumption for separation (the total load of the reboilers of distillation columns), sсheme I (a traditional complex of extractive distillation) is recommended. Additionally, the energy expended for the separation of the basic equimolar mixture using glycerol as the extractive agent was compared with that expended using another selective agent: 1,2-ethanediol. Glycerol is an effective extractive agent because it reduces energy consumption, in comparison with 1,2-ethanediol, by more than 5%.